Kangaroo Method Treatment Increases Baby's Body Temperature With Low Birth Weight - Kurniasih, Fenny Dwi; Nugroho, Heryanto Adi; Chanif, Chanif (University of Muhammadiyah Semarang, 2020)
Birth weight is less than 2500 grams which contribute to infant mortality especially during the perinatal period, one of the interventions that can be done with kangaroo method, this method can make the baby's body temperature stable because the baby who is in the care of the kangaroo method will feel like it exists in the uterus of the mother, in addition to the treatment of kangaroo methods aimed at helping to accelerate the process of increasing the baby's body temperature as well as being able to stabilize the body temperature in babies who experience low birth weight. The design of the study used is a descriptive method with a case study approach of nursing care using a pre and post-test design conducted on 2 respondents. Before being given the kangaroo method 1 respondent and respondent 2 experienced low weight measured using observation sheet for 3 days while after being given kangaroo method respondent 1 and respondent 2 experienced weight gain measured using observation sheet for 3 days characterized by normal weight. Kangaroo treatment therapy method can increase body temperature in babies with low birth weight in the perinatology room of K.R.M.T Wongsonegoro Hospital Semarang.